Genetic and metabolic engineering of medium chain fatty acids synthesis in yeast : role of thioesterases. - Lee, Benedict Jia Hong. (2013)
In this project, we demonstrated the genetic engineering of POX deletion strains of S. cerevisiae (baker’s yeast) through the heterogeneous expression of thioesterases to produce medium chain fatty acids in S. cerevisiae cells. The thioesterases expressed in S. cerevisiae were chosen for its specificity for medium chain fatty acids phenotype in order to terminate fatty acid synthesis at the desired chain length of C8-C12. The cDNA sequences coding for these enzymes were first chemically synthesized and cloned into expression vectors for transformation into the POX deletion strains of S. cerevisiae.